Efektifitas Pelaksanaan Penundaan Kewajiban Pembayaran Utang (PKPU) dalam Mencegah Kepailitan (Studi Pengadilan Niaga pada Pengadilan Negeri Jakarta Pusat) - Ratu Alawiyyah Rifani; Fauziah Fauziah; Muhammad Fahruddin (Jurnal Hukum Jurisdictie, 2021)
The results showed that the Postponement of Debt Payment Obligations or PKPU means that it can be used by debtors to avoid bankruptcy. So before declared as bankruptcy, debtors can apply for PKPU. PKPU applications are submitted to the Commerrcial Court established within the General Court. In 2017, 2018 and 2019 the Commercial Court at Central Jakarta District Court has received many incoming PKPU case reports and continues to increase every year. PKPU that has been accepted and determined can be submitted as a peace plan by the debtor, the peace plan is submitted to resolve debt settlement disputes between debtors and creditors, PKPU can be considered effective if PKPU submitted by the debtor ends with peace. In addition, the driving factor for PKPU's effectiveness in preventing bankruptcy is the content of the peace agreement that has been homologated by the Commercial Court.